Cystinosis: electron microscopic evidence of lysosomal storage of cystine in lymph node. Issue 5 (September 1968) - Patrick, A. D.; Lake, B. D.
Abstract : Electron microscopic examination of a biopsy specimen of cystinotic lymph node demonstrated that cystine crystals were entirely intracellular, and that the majority, including those of the largest size, were enclosed by intact limiting membranes. Acid phosphatase activity was localized specifically at the periphery of the crystal profiles and the smallest crystal aggregates were contained in osmophilic dense bodies which had the appearance of progressively swollen lysosomes. The implications of the suggested lysosomal distribution of cystine are discussed.